2009
DOI: 10.1002/chem.200902094
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conjugate Additions of Geminal Bis(sulfone)s: Expanding the Chemistry of Sulfones as Simple Alkyl Anion Equivalents

Abstract: The value of cyclic gem-bis(sulfone) 4 as a simple alkyl nucleophile equivalent in catalytic C-C bond-forming reactions is demonstrated. The 1,4-type nucleophilic additions of bis(sulfone) 4 to alpha,beta-unsaturated ketones take place by assistance of catalytic guanidine base. On the other hand, pyrrolidines are able to catalyze the conjugate addition of 4 to both enones and enals, likely by means of iminium ion activation. Upon exploration of the best chiral pyrrolidine catalyst, it has been found that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 63 publications
0
14
0
1
Order By: Relevance
“…Although excellent enantioselectivity was obtained with cinnamaldehydes, enantioselectivity decreased with aliphatic enals (90.0:10.0 enantiomeric ratio (e.r.) in the reaction of crotonaldehyde) 23c. Aleman and co‐workers reported the reaction using diphenylprolinol TMS ether ( 1 ) in the presence of LiOAc in THF, and excellent enantioselectivities were obtained in most of the reactions except for crotonaldehyde, which afforded the product in 90.0:10.0 e.r 23a.…”
Section: Resultsmentioning
confidence: 99%
“…Although excellent enantioselectivity was obtained with cinnamaldehydes, enantioselectivity decreased with aliphatic enals (90.0:10.0 enantiomeric ratio (e.r.) in the reaction of crotonaldehyde) 23c. Aleman and co‐workers reported the reaction using diphenylprolinol TMS ether ( 1 ) in the presence of LiOAc in THF, and excellent enantioselectivities were obtained in most of the reactions except for crotonaldehyde, which afforded the product in 90.0:10.0 e.r 23a.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of cyclization for the enantioselectivity of 4. was mainly converted into the diastereomers of 5. [18] After examining the reaction conditions, the addition of benzoic acid [19] was found to be effective for obtaining cyclic compound 5 as a major product (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…The sulfone was used as an activated methylene compound in the Michael reaction of a,b-unsaturated aldehydes reported by Palomo and co-workers in 2009 [49] The screening of iminium catalysts revealed that silyl ether 13a was effective in the reaction of sulfone and cinnamaldehyde with good yield and excellent enantioselectivity (Scheme 23).…”
Section: Active Methylene Compounds As Donormentioning
confidence: 97%